The influence of Brazilian exports on price transmission processes in the coffee sector: A Markov-switching approach - Teresa Vollmer; Stephan von Cramon-Taubadel (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2019)
Most analysis of agricultural commodity market integration is solely based on price information. However, adding trade data can improve the understanding of interactions between interrelated markets. We link the analysis of price transmission processes between spot and futures markets with trade information to study the influence of Brazilian coffee exports on global price interdependencies. Using a Markov-switching vector error correction model (MSVECM) we allow for structural changes over time. Our results reveal two regimes. One regime is characterized by periods of sideways or downward trending coffee prices with low price volatility, and the other one by phases of price spikes and high price volatility. Price information is transmitted through both the spot and the futures prices and the speed of the price transmission process is significantly affected by the total daily volume and value of Brazilian coffee exports.
Keywords: 330; price transmission; Markov-switching models; coffee; customs data; spot and futures markets